Pengaruh Harga dan Permintaan Terhadap Persediaan Air Bersih Depot Tri Santa Bagi Masyarakat Dalam Kota Ende - Yosef Moan Banda; Adri Manggo Lando (Ekspektasi: Jurnal Pendidikan Ekonomi, 2020)
The availability of clean water for Tri Santa Depot with the demand for clean water for the people in Ende city and the selling price influences the purchasing power of the community. To find and analyze the joint effect between price and demand for clean water supplies. In abtaining data, quantitative research using inductive statistical approaches is used. Data collection techniques are questionnaire, with a sample of 20 cuatomers. The sampling technique is purposive sampling. The result of the data analysis show that there is a joint effect od selling prices and demand for clean water supplies. This is indicated by calculated F value> F table or 4.25 > 3.59.